Benign schwannoma of the tonsil - Joseph, J A (BMJ Publishing Group, 2010)
The case of a rare tumour in a rare location is presented, and important aspects of the management of similar clinical scenarios are highlighted. Tonsillar schwannoma is a slow growing lesion presenting in the third to fifth decade of life. Histological diagnosis is made through the identification of Antoni A (Verocay bodies) and Antoni B cells with S-100 expression. A 24-year-old man presented with a 5 cm right tonsillar tumour causing dysphagia and dysphonia for 6 weeks. Tonsillar schwannoma can be diagnosed in the outpatient clinic. CT imaging and tissue biopsy are the appropriate investigations followed by complete surgical enucleation. Schwannoma has the potential for malignant transformation, with no recorded cases of this occurring in the tonsil.